Improving farm-level antimicrobial stewardship benchmarks by reporting antimicrobial use within the context of both the magnitude of disease pressure and the outcome of therapy - Schrag, Nora F. D.; Godden, Sandra M.; Singer, Randall S.; Lombard, Jason E.; Wenz, John R.; Amrine, David E.; Lubbers, Brian V.; Apley, Michael D. (Frontiers in Veterinary Science, 2022)
This manuscript explores a method of benchmarking antimicrobial use within the context of farm level therapeutic incidence (a proxy for disease incidence), and the outcome of that therapy. This is reported both within the same farm over time (2016-2019), as well as evaluated across participating farms. Reporting antimicrobial use in this format addresses multiple primary questions necessary for evaluating on farm antimicrobial stewardship: How much disease is recorded? How much antimicrobial use is recorded? How often are antimicrobials included in therapy for each disease? What is the outcome of therapy? The three primary metrics reported are: therapeutic events per 100 cow years (TE/100CY), antimicrobial regimens per 100 cow years (REG/100CY), and the percent therapeutic success (% Success). Success was defined as: the cow remained in the herd and had no further TE recorded within 30 days of the end of the TE being evaluated. These measures identify opportunities for change on an individual farm, such as improvement in disease prevention, or a change in choices about when to include an antimicrobial in the treatment protocol. Therapeutic outcomes provide additional context, in some instances demonstrating differences in recording practices and case definitions, while in other cases serving to safeguard animal welfare as efforts are made to decrease antimicrobial use in the future. Although developed for farm level reporting, the metrics may also be more broadly summarized to meet future reporting requirements for marketing chain or national level antimicrobial use reports. The process outlined here serves as a prototype to be considered when developing antimicrobial use reporting systems where farm level antimicrobial stewardship is the primary objective.